Comparison between adenosine triphosphate bioluminescence and aerobic colony count to assess surface sanitation in the hospital environment (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Adenosine triphosphate bioluminescence produced by the firefly luciferase has been successfullyintroduced to verify cleaning procedures in the food industry according to the Hazard Analysis Critical Control Pointprogram.Our aim was to evaluate the reliability of bioluminescence as a tool to monitor the effectiveness of sanitation in healthcaresettings, in comparison with the microbiological gold standard.Methods: 614 surfaces of various material were randomly sampled in Policlinico University Hospital units in Palermo,Italy, to detect adenosine triphosphate bioluminescence and aerobic colony count. Linear regression model andPearson correlation coefficient were used to estimate the relationship between the two variables of the study.Results: Aerobic colony count median was 1.71 colony forming units/cm2 (interquartile range = 3.8), whereasadenosine triphosphate median was 59.9 relative light units/cm2 (interquartile range = 128.3). Pearson coefficientR2 was 0.09. Sensitivity and specificity of bioluminescence test with respect to microbiology were 46% and 71%,whereas positive predictive value and negative predictive value were 53% and 65%, respectively.Conclusion: According to our results, there seemed to be no linear correlation between aerobic colony countand adenosine triphosphate values, suggesting that current bioluminescence technology has not any proportionalrelationships with culturable microbes contaminating environmental surfaces in health-care settings.
Keywords: Bioluminescence; Sanitation; Surfaces; Cleaning Monitoring